The Influence of Promotions and Discounts on Customer Satisfaction in GrabFood and GoFood: A Case Study of Business Administration Students at Universitas Sam Ratulangi - Rungkat, Angelica; Pendong, Mikhael; Tumiwang, Marcellino; Mamuaya, Intan; Asaloei, Sandra Ingried (Yayasan Bina Lentera Insan, 2025)
This research aims to investigate the influence of promotions and discounts on students' preferences in using food delivery services, specifically GoFood and GrabFood. A quantitative method was employed in this study, with data collection conducted through questionnaires distributed to a sample of students. The results of data analysis indicate that promotions and discounts have a significant impact on students' decisions in choosing between GoFood and GrabFood. Students tend to prefer services that offer more attractive promotions and discounts. Additionally, factors such as ease of app usage, delivery speed, and menu variety also play crucial roles in influencing students' preferences. This research provides valuable insights for food delivery service providers like GoFood and GrabFood to design more effective promotion and discount strategies in attracting student customers. Furthermore, this research can serve as a reference for further studies in understanding consumer behavior in the food delivery industry.